How to avoid risks for patients in minimal-access trials: Avoiding complications in clinical first-in-human studies by example of the ADBEE study. (August 2016) - Cezar, Cristina; Korell, Matthias; Tchartchian, Garri; Ziegler, Nicole; Senshu, Kazuhisa; Herrmann, Anja; Larbig, Angelika; De Wilde, Rudy Leon
Abstract : A clinical trial is a prospective study designed to establish the safety and efficacy of investigational devices in humans, in accordance with the strict guidelines of the Food and Drug Administration (FDA; USA) or European Medicines Agency (EMA; Europe). Before a clinical first-in-human study is initiated, preclinical studies of the investigational product are mandatory, and the results should be sufficient to indicate that the investigational device is acceptably safe for the proposed evaluation in human subjects. The present paper describes an experience of clinical trials, highlighting ways of avoiding possible complications in clinical first-in-human studies. For a better approach to our aim, we exemplified a prospective, randomized, single-blind study, ADBEE. The primary objective was to assess the safety of the ADBLOCK system when used as an adjunct to laparoscopic primary removal of myomas in women wishing to improve pregnancy outcomes. Highlights: Our experience of clinical trials, highlighting ways of avoiding possible complications in clinical first-in-human studies. We exemplified a prospective, randomized, single-blind study, ADBEE, carried out in three different centers in Germany. Preclinical studies for ADBEE provided evidence of safety and efficacy of the ADBLOCK reducing adhesions in animal models. The first-in-human clinical trial of the ADBEE study has reached its end point in terms of safety.